The picture of reading: Deriving meaning in literacy through image. - Piro, Joseph M. (Reading Teacher, 2002)
Focuses on the strategy of reading a picture and how it fits in promoting a culture of literacy. Similarities between language arts and visual arts; Application of the reader-response theory in the use of pictures as text; Steps involved in reading a picture.